Livestock grazing constrains bird abundance and species richness: A global meta-analysis - Barzan, Flavia R.; Bellis, Laura M.; Dardanelli, Sebastián (Basic and applied ecology, 2021)
Balancing food production and biodiversity conservation is a global challenge today. Livestock grazing is one of the main activities triggering habitat degradation and land-use change around the world. Its effects on biodiversity have been widely explored, with birds being the most studied vertebrates. However, its impact seems to be contradictory given the disparity of the results. To understand the influence of livestock grazing on birds, we conducted a meta-analysis exploring the effects of several grazing characteristics on bird abundance and species richness. Our results showed that livestock grazing has a significant negative effect on bird abundance (mean effect size -0.422 ± 0.140), and species richness (mean effect size -0.391 ± 0.141). Livestock grazing affected negatively the bird abundance in riparian habitats in contrast to the other habitat types. Species richness was negatively affected by grazing in woody habitats and Afrotropical and Neotropical regions. Grazing by cattle was more detrimental for both bird richness and abundance than sheep grazing or a mixture of domestic livestock. Moreover, intermediate grazing intensity seems appropriate to maintain bird abundance and richness, as high grazing intensity dropped both bird abundance and species richness substantially, and low grazing intensity reduced bird species richness. This pattern supposes a non-linear effect of grazing intensity on birds. Therefore, the management of grazing intensity and type of livestock could help to reduce the negative effect on bird abundance and richness, as moderate grazing intensities and mix of livestock types appear to have a minor or null impact on bird abundance and richness. Future studies should explore in-depth the effect of moderate grazing intensities on bird diversity and composition to provide better management recommendations to enhance avian conservation in rangelands. [Display omitted]